Parent-child interaction and children's learning from a coding application - Sheehan, Kelly J.; Pila, Sarah; Lauricella, Alexis R.; Wartella, Ellen A. (Computers and education, 2019)
Research suggests that children can learn educational concepts from well-designed applications (apps), including foundational science, technology, engineering, and math (STEM) concepts. Parents may be important for promoting children's STEM learning from touchscreen apps, as parents can help their children learn from other media. However, little research has explored how parents and children use coding apps together for learning, and whether specific parent-child interactions in these contexts promote children's learning from apps. Therefore, we observed 31 parents and their 4.5- to 5.0-year old children playing a coding app together and coded for spatial talk, question-asking, task-relevant talk, and responsiveness. Results show that parents and children engaged in high-quality interactions during coding app play, with parents and children exhibiting high responsiveness and task-relevant talk, and parents exhibiting a higher proportion of question-asking and spatial talk compared to their children. Importantly, linear regression analyses show that the dyad's ability to stay on task during the coding task predicts children's learning of coding, while question-asking was a negative predictor of children's learning. These results suggest that coding apps may be a rich context for STEM learning, and that specific parent-child interactions can scaffold their children's learning from STEM apps. •4.5- to 5-year-olds were observed playing a coding app, ScratchJr, with a parent.•We coded play for responsiveness, spatial talk, task-relevancy and questions.•Dyads performed at ceiling on responsiveness measures during play.•Parents used more spatial talk and asked more questions compared to children.•Task-relevancy predicted coding learning; question-asking was a negative predictor.